Self-construal moderates age differences in social network characteristics. - Yeung, Dannii; Fung, Helene H.; Lang, Frieder (Psychology and Aging, 2008)
In this study, the authors examined age differences in social network characteristics (SNC) among Hong Kong Chinese. The sample consisted of 596 Chinese adults, ranging from 18 to 91 years old. Age was positively associated with close social partners and negatively associated with peripheral social partners. For individuals who were more likely to define the self as interconnected with others (i.e., interdependent self-construal), increasing age was associated with a greater number of close social partners. The negative association between age and the number of peripheral social partners, well-documented in the Western literature, was found only among Chinese adults with lower interdependence but not among those with higher interdependence. These findings highlight the importance of examining the underlying mechanism rather than a particular pattern of SNC across cultures.